Early signs of COVID-19 in Pakistan - Taimur Mahmood; Moiz Javed; Raina MacIntyre; Aye Moa (University of New South Wales, 2021)
'Background: 'The outbreak of novel coronavirus (COVID-19) has turned into a public health emergency of international concern. With no antiviral drugs nor vaccine, presence of carriers without obvious symptoms and varied clinical characteristics, the traditional public health measures are certainly less effective. The early signs of COVID-19 and epidemiological data are essential to strengthen the overwhelmed healthcare systems. 'Aim:' To detect, assess and analyse the early signs of COVID-19 in Pakistan before the official reporting of cases in the country. 'Methods:' The study uses the EpiWATCH observatory to extract data from 1 November 2019 to 1 April 2020. The trend of pneumonia of unknown origin cases in Pakistan was observed to assess if cases of COVID-19 could have been detected before the first official case was reported. A descriptive analysis of the obtained data was achieved on the basis of geographic and demographic features. 'Results:' A total of 151 entries were included in the study. Before the identification of the first official case of COVID-19 in Pakistan, 54 reports of cases of pneumonia of unknown origin were recorded. After the first case of COVID-19 was reported, 97 reports of cases of COVID-19 were recorded. The study findings suggest that there were early signs of COVID-19 in Pakistan since the second week of January 2020, a month and a half prior to the first case being reported in the country.